2011
DOI: 10.1002/chem.201101679
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐Eutectic‐Solvent‐Assisted Synthesis of Hierarchical Carbon Electrodes Exhibiting Capacitance Retention at High Current Densities

Abstract: Nature provides a wide range of entities and/or systems with different functions that may serve as a source of bioinspiration for material chemists. Actually, materials exhibiting a 3D porous texture (combining pores at different scales, from macro-to meso-up to micropores) mimic the hierarchical structure of different systems found in living organisms (e.g., the blood circulation or the respiratory system in mammalians). Structural organization at different scales is ultimately responsible for the outstanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 71 publications
0
83
0
Order By: Relevance
“…IL based syntheses of carbon materials have been established in manifold ways in recent years of research. [1][2][3][4][5][6][7][21][22][23][39][40][41][42][43][44][45][46][47][48] Especially liquid salts with dicyanamide anions are a powerful precursor for N-doped carbons, [1][2][3][4][5][6][7] and for advanced co-doping with S. 27 Herein we present a modified IL route using phosphonium additives, paving the way towards P-and N-co-doped carbonsa class of materials only rarely reported in the literature so far. 36 BMP-dca with 40 mol% of tetrabutyl-phosphonium-bromide (TBuPBr) as a phosphorus source was therefore carbonised at 1000 1C in a constant flow of inert gas (see ESI † for details).…”
mentioning
confidence: 99%
“…IL based syntheses of carbon materials have been established in manifold ways in recent years of research. [1][2][3][4][5][6][7][21][22][23][39][40][41][42][43][44][45][46][47][48] Especially liquid salts with dicyanamide anions are a powerful precursor for N-doped carbons, [1][2][3][4][5][6][7] and for advanced co-doping with S. 27 Herein we present a modified IL route using phosphonium additives, paving the way towards P-and N-co-doped carbonsa class of materials only rarely reported in the literature so far. 36 BMP-dca with 40 mol% of tetrabutyl-phosphonium-bromide (TBuPBr) as a phosphorus source was therefore carbonised at 1000 1C in a constant flow of inert gas (see ESI † for details).…”
mentioning
confidence: 99%
“…[ 28 ] In this case, electrodes can be either bare carbon or carbon-carbon nanotube nanocomposite foams, the preparation of which with a hierarchical structure (such as those found in Nature) is not based on ice segregation but on the segregation (in a spinodal decomposition-like process) of a certain compound that, besides the carbonaceous precursor, forms a deep eutectic solvent (DES). [ 29 ] It is worth noting that the recovering of one of DES counterparts (and its reutilization in subsequent synthetic reactions) confers an interesting ''green'' character to this sort of synthetic processes. [ 30 ] …”
Section: Research Newsmentioning
confidence: 99%
“…Gutiérrez et al 47 achieved enhanced performance in CNT-based aerogels by adapting the organic sol-gel method to deep eutectic solvents (DESs) that readily disperse CNTs. Gutiérrez et al report that DESs catalyze the polycondensation of furfuryl alcohol to form a bicontinuous porous architecture consisting of colloidal particles.…”
Section: B Cnt Aerogelmentioning
confidence: 99%
“…Thus by using the RF sol-gel method to form sp 2 carbon junctions between CNTs, CNT aerogels that simultaneously exhibited good electrical conductivity and mechanical robustness were realized. 42,47,48 Recently, De Marco et al 49 demonstrated another route to synthesis of CNT aerogels with covalent carbon bonds starting from SWCNT anions in N,N-dimethylacetimide (DMAc). A major advantage of working with SWCNT anions in DMAc is that one can start with a true solution of individualized CNTs at high concentrations without damaging the CNTs with sonication or oxidation.…”
Section: B Cnt Aerogelmentioning
confidence: 99%